Current knowledge on Parmelia genus: Ecological interest, phytochemistry, biological activities and therapeutic potential - González Burgos, Elena María; Fernández Moriano, Carlos; Gómez-Serranillos Cuadrado, María Pilar (Phytochemistry, 2019)
Parmelia Acharius is one of the most representative genera within Parmeliaceae family which is the largest and the most widespread family of lichen-forming fungi. Parmelia lichens present a medium to large foliose thallus and they are distributed from the Artic to the Antartic continents, being more concentrated in temperate regions. According to its current description, the genus encompasses up to 41 different species and it is phylogenetically located within the Parmelioid clade (the largest group in the family). Interestingly, some of its species are among the most common epiphytic lichens in Europe such as Parmelia sulcata Taylor and Parmelia saxatilis (L.) Ach. The present work aims at providing a complete overview of the existing knowledge on the genus, from general concepts such as taxonomy and phylogeny, to their ecological relevance and biological interest for pharmaceutical uses. As reported, Parmelia lichens arise as valuable tools for biomonitoring environmental pollution due to their capacity to bioaccumulate metal elements and its response to acid rain. Moreover, they produce a wide array of specialized products/metabolites including depsides, depsidones, triterpenes and dibenzofurans, which have been suggested to exert promising pharmacological activities, mainly antimicrobial, antioxidant and cytotoxic activities. Herein, we discuss past and recent data regarding to the phytochemical characterization of more than 15 species. Even though the knowledge is still scarce in comparsion to other groups of organisms such as higher plants and other non-lichenized fungi. Reviewed works suggest that Parmelia lichens are worthy of further research for determining their actual possibilities as sources of bioactive compounds with potential therapeutic applications. Depto. de Farmacología, Farmacognosia y Botánica Fac. de Farmacia TRUE pub